La transformation des friches à l’épreuve de l’adaptation des territoires au changement global - Samia Sediri; Marc Kaszynski; Michel Trommetter; Nathalie Frascaria-Lacoste (Développement Durable et Territoires)
Adaptive capacity is increasingly recognized as essential for building the resilience of the nested social-ecological systems under global change. Enhancing adaptive capacity through appropriate land (re)use planning, including wastelands transformation, could help societies and ecosystems to mitigate change and adjust to the inevitable impacts of climate change, at local and even regional scales. Our objective is to show why the adoption of a systemic perspective based on social-ecological systems, can offer a relevant framework, in order to consider wastelands transformation to achieve desirable and sustainable futures of territories. Herein, we argue the necessity for such a transformation strategy and provide examples from literature, with regard to the social and ecological adaptive capacity that enables social-ecological adaptation.